Anticancer Potency of Copper(I) Complexes Against a Range Cancer Cell Lines: A Review - Singh, Narendra Kumar; Yadav, Paras Nath (Journal of Institute of Science and Technology, 2021)
The copper(I) complexes of N,N-diimine, N,O- and/or N, S-bidentate systems perform significant dose-dependent anticancer activity toward various cell lines viz. MCF-7, LNCap, PSN-1, A431, BxPC3, H157, A2780, HeLa, MDA-MB231, MGC-803 etc. The copper(I) complexes can cross the cellular plasmalemma that results in the accumulation of copper ion in the cancer cells, exhibit significant anticancer effect and overcome the multidrug resistance because these can slightly induce the DNA cleavage as a result of limited generation of reactive oxygen species (ROS). Copper(I) complexes exhibit significantly higher broad-spectrum antiproliferation and cell apoptosis via mitochondrial pathway than that of their corresponding Cu(II), Co(II), Pd(II), and Ni(II) complexes. The copper(I) complexes inhibit the cancer cells not only via ROS generation but also via DNA interactions possibly by attacking the sugar-phosphate backbone of DNA due to their oxidative and partial dissociation behavior. Copper(II/I) complexes are also able to cleave DNA by hydrolytic pathway and induce caspase-dependent-mitochondrial-mediated cell apoptosis by ROS production or blocking the progression of cell cycles. In many cases, the modification in organic moiety and the placement of electronegative substituent near the metallic center of complexes have been found to enhance their anticancer potency in a significant manner. Thus copper(I) complexes may be used as the better anticancer drugs with multiple modes of action compared to the copper(II) complexes due to having oxidative behavior and generation of empty site on copper(I) ion during partial dissociation.